Effects of alloyed La, Cu and B on the oxidation of Fe-22Cr ferritic stainless steels under simulated cathode side atmosphere of solid oxide fuel cell interconnects - Swaminathan, Srinivasan; Lee, Young-Su; Kim, Dong-Ik (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Discontinuous oxidation of La (0.14-0.52 wt.%), Cu (0.17-1.74 wt.%) and B (48-109 ppm) alloyed Fe-22Cr ferritic stainless steels, and Crofer 22 APU (0.047 wt.% La), have been studied at 800 degrees C, in flowing air-2% H2O atmosphere, for 1300 h. The determined parabolic rate constants (1.65-2.58 x 10(-4) me cm(-4) h(-1)) are quite close to each other. Benefits of high La-alloying are not caused by the reduction in oxidation, but rather by the alteration in scale growth direction. On the other hand, high Cu-alloying promotes the segregation of Cu at the scale/alloy interface, which suppresses the sub-surface and/or internal oxidation.
Keywords: HIGH-TEMPERATURE OXIDATION; CROFER 22 APU; METALLIC INTERCONNECTS; SOFC INTERCONNECT; RESISTANT ALLOYS; STAGE OXIDATION; SCALE; BEHAVIOR; CR; HEAT